2013
DOI: 10.2753/ree1540-496x490402
|View full text |Cite
|
Sign up to set email alerts
|

Local Financial Development and Household Welfare: Microevidence from Thai Households

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Following Bernd Hardeweg and Hermann Waibel, a household includes the household head and all persons who live in the household for at least 180 days per year (2009). All these persons were defined as nucleus household members (Gloede and Rungruxsirivorn 2013).…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…Following Bernd Hardeweg and Hermann Waibel, a household includes the household head and all persons who live in the household for at least 180 days per year (2009). All these persons were defined as nucleus household members (Gloede and Rungruxsirivorn 2013).…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…For example, studies have examined the impact of microcredit on welfare (Khandker, 1998;Morduch, 1998;Akotey & Adjasi, 2016) and the impact of access to welfare via its effects on consumption smoothing (Bae, Han, & Sohn, 2012;Gloede & Rungruxsirivorn, 2013;Hacamo, 2014). In micro-analysis studies, overindebtedness is indicated by debt repayments that are greater than the income poverty line, which clearly reveals the link between debt and poverty (Russell et al, 2011;D'Alessio & Iezzi, 2013;Ntsalaze & Ikhide, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…This impact has been observed in various contexts, including in the Mezam district of North-West Cameroon where Atamja and Yoo (2021) found that households that either save formally or informally increase their consumption level, and hence their welfare. Access to finance has also been found to have positive impacts on overall household expenditure in India (Shetty, 2008), household investment in Thailand (Gloede & Rungruxsirivorn, 2013), income (Addury, 2018;Ibrahim & Aliero, 2020;Shetty, 2008), as well as assets and empowerment (Nanziri, 2018;Shetty, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%